The Influence of Digital Talent and Green Innovation and Its Impact on the MSME Business Model in the Metaverse Era - Reniati, Reniati; Bidayani, Endang; Sumiyati, Sumiyati (Universitas Mercu Buana, 2023)
Objectives: The study aims to look at MSME Business Models Entering the Metaverse Era Through Digital Transformation with an Increase of Digital Talent and Green InnovationMethodology: The type of research used is quantitative research. A study was carried out in 5 regencies/cities on Bangka Island with respondents 10 2 SMEs, dominated in the culinary sector. In this study, the author uses the analytical method used to test the PLS (Partial Least Square) variable using SmartPLS software. The path analysis model of all latent variables in Partial Least Square (PLS) consists of an outer model, convergent validity, and discriminant validity which is then carried out with a reliability test and a structural model consisting of coefficient of determination (R 2 Value), Effect Size (f 2), and Predictive Relevance (Q2 Value). Ending with a test on the hypothesis and the moderating effect.Conclusion: The results of this study indicate that hypothesis testing concluded that two research hypotheses are accepted and the other three are rejected. The accepted research hypotheses are Digital Talent effect on Digital Transformation and Digital Talent effect on MSME Business Model in the Metaverse Era. These results indicate that only digital talent currently contributes significantly to Digital Transformation and the MSME business model in the metaverse Era.